Designing hardware for a robust high-speed cryptographic key generator based on multiple chaotic systems and its FPGA implementation for real-time video encryption - Ince, Esra; Karakaya, Baris; Turk, Mustafa (Springer, 2024)
Recent advancements in communication technologies have highlighted the pivotal role of information security for all individuals and entities. In response, researchers are increasingly focusing on cryptographic solutions to ensure the reliability of confidential information. Recognizing the superiority of chaotic systems preference as entropy source of cryptographic systems, this paper proposes a novel true random number generator (TRNG) design by combining four different chaotic systems outputs, tailored for real-time video encryption application. These chaotic systems are continuous-time Lorenz and fractional-order Chen-Lee systems, as well as discrete-time Logistic and Tent maps. This study generates true random bit (TRB) sequences at a high bit rate (25 Mbps) through the hardware implementations of four distinct chaotic systems to have the best statistical randomness in the resulting output. Then, the cryptographic true random key bits (8-bit at 25 MHz frequency) are employed in the post-processing with real-time video data by using the XOR operation, a fundamental post-processing algorithm. The real-time video encryption application is executed on an experimental assembly, composed of a Field Programmable Gate Array (FPGA) development kit, an OV7670 camera module, a VGA monitor, and prototype circuit boards for the chaotic systems. To evaluate the effectiveness of the proposed encryption system, several security assessments are conducted. These include NIST SP 800 - 22 statistical tests, FIPS 140-1 standards, chi-square tests, histogram and correlation analysis, and NPCR and UACI differential attack resilience tests. Consequently, the findings suggest that the presented real-time embedded cryptosystem is robust and suitable for secure communications, particularly in the realm of video transmission.
Keywords: Chaotic map; Fractional-order; Post-processor; Random number bit generator; Statistical tests; Video encryption